A Translator’s Wanderings in TranslationStudiesWorld - Mossop, Brian (TTR, 2017)
This semi-autobiographical article reflects on the discipline known as Translation Studies from the point of view of the author, who was a full-time Canadian government translator from 1974 to 2014, but also taught and wrote about translation. The narrative begins with the emergence of Translation Studies in Canada and in Europe and continues through the present neoliberal era, with reflection on a variety of topics including the English name of the discipline, the lack of definition of an object of study, the original role of the journal Meta, and the notion of translation as applied linguistics. The last section considers two fictive scenarios in which Translation Studies does not emerge, and translation is studied, right from the start, in ways much more closely linked to the translation profession, with a focus on translators rather than translations, and therefore on translational production rather than the analysis of completed translations.